Developmental Validation of DNA Quantitation System, Extended STR Typing Multiplex, and Database Solutions for Panthera leo Genotyping - Vankova, Lenka; Alaverdyan, Johana; Vanek, Daniel (Life (Basel, Switzerland), 2025)
This study describes the development of a species determination/DNA quantification system called Pleo Qplex and an individual identification STR multiplex called Pleo STRplex using Panthera leo samples. Pleo Qplex enables us to measure the quantity of extracted nuclear and mitochondrial DNA and detect the presence of co-purified inhibitors. Pleo STRplex, consisting of seven loci, enables the determination of the DNA profile from a sample of Panthera leo based on the analysis of short tandem repeats (STRs). The Pleo STRplex provides additional loci on top of previously published STR loci in Ptig STRplex and contains a specific STR marker that confirms Panthera leo. An allelic ladder of all STR markers was prepared to enable reliable allele calling. The STR loci can also be used to type the DNA of other members of the genus Panthera. The work on the resulting STR profiles is performed using GenoProof Suite, which offers databasing, matching, and relationship analysis.
Keywords: wildlife; CITES organism; DNA quantitation; matching analysis; species determination; databasing; STR multiplex; forensic genetics